A Poem by Guarino on Leonello of Ferrara. (2014) - Hays, Gregory
Abstract : This article revisits a set of sixteen hexameters by Guarino on the accession of Leonello d'Este in 1442. The poem was first published by Ian Thomson, whose text can be improved in several minor points as well as one major one. Thomson had already realized that Guarino's lines are not transmitted in their original order and had proposed to move lines 4–6 to follow line 11. The displacement is in fact even more extensive than he realized but has a simple mechanical explanation and a simple solution. Once the lines are properly distributed, the piece emerges as a dialogue between an unnamed speaker and the city of Ferrara, perhaps intended to accompany a visual representation of some sort. Thomson's theory that Guarino ghost-wrote the poem for an unnamed presbyter to present to Leonello is shown to be problematic.